2020
DOI: 10.1101/2020.02.25.964676
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Anticipatory energization revealed by pupil and brain activity guides human effort-based decision making

Abstract: 17An organism's behavioral success is determined by its ability to mobilize resources to overcome 18 challenges. This ability involves the noradrenergic system, indicated by the finding that pupil-size 19 increases proportionally with currently exerted effort. However, humans can deliberate in advance 20 whether to engage in effort in the future. It remains unclear how effort is represented in such an 21 anticipatory fashion during decision-making. We investigated this by measuring pupil responses while 22 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 82 publications
1
1
0
Order By: Relevance
“…Importantly, the current study tested the relationship between task difficulty and pupil size during a cue period and not during task performance. As such, pupil size tracked the average accuracy of the upcoming task, consistent with previous accounts (Kurniawan, Grueschow & Ruff, 2021) which dissociated the time of effort anticipation from that of effort exertion in an instrumental effort paradigm and showed that pupil size tracked the anticipation of the upcoming effort level of the task in a voluntary choice paradigm. Moreover, these increases in pupil dilation were stronger when the participants accepted to exert the effort option versus not, suggesting that pupil size might be associated with the energization required to perform an upcoming action.…”
Section: Discussionsupporting
confidence: 89%
“…Importantly, the current study tested the relationship between task difficulty and pupil size during a cue period and not during task performance. As such, pupil size tracked the average accuracy of the upcoming task, consistent with previous accounts (Kurniawan, Grueschow & Ruff, 2021) which dissociated the time of effort anticipation from that of effort exertion in an instrumental effort paradigm and showed that pupil size tracked the anticipation of the upcoming effort level of the task in a voluntary choice paradigm. Moreover, these increases in pupil dilation were stronger when the participants accepted to exert the effort option versus not, suggesting that pupil size might be associated with the energization required to perform an upcoming action.…”
Section: Discussionsupporting
confidence: 89%
“…pupil constriction in response to brightness changes, whereas the sympathetic pathway controls dilation in response to arousal (Loewenfeld, 1958). Arousal could for example be caused by emotionally salient stimuli, but also be recruited in order to meet cognitive demands (Aston-Jones & Cohen, 2005;Eldar, Cohen, & Niv, 2013, 2016Mather, Clewett, Sakaki, & Harley, 2016;Verguts & Notebaert, 2009) or in order to mobilize effort (Kurniawan, Grueschow, & Ruff, 2020;Varazzani et al, 2015;Walton & Bouret, 2019). Previous studies have also reported that pupil diameter increases when individuals regulate their emotions (Johnstone, van Reekum, Urry, Kalin, & Davidson, 2007;Kinner et al, 2017;Richey et al, 2015;Urry, 2009;Urry et al, 2006;.…”
Section: Introductionmentioning
confidence: 99%